2022
DOI: 10.1038/s41598-022-23545-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Tisochrysis lutea on dry eye syndrome via NF-κB inhibition

Abstract: Dry eye syndrome (DES) affects the cornea, causes pain and hypersensitivity to light. Although inflammation and endoplasmic reticulum stress are known to be involved, the detailed mechanisms remain unknown. DES is characterized by a decrease in corneal thickness, tear volume, and lacrimal gland size, and damage to corneal cells. Tisochrysis lutea is a microalga that has been shown to reduce immune factors. Therefore, we hypothesized that T. lutea could ameliorate DES. We investigated the role of T. lutea in sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
1
3
1
Order By: Relevance
“…The short-term nature of the clinical follow-up, especially in the efficacy study, restricts our ability to assess the long-term effects of the helenalin-based formulation. On the other hand, the rapid and multi-targeted efficacy of the studied formulation aligns with previous outcomes of similar studies that blocked NF-κB/TNF-α pathways [ 65 , 74 , 75 ]. It is important to recognize that the rapid improvement observed in this study may not be representative of the standard response across all DED therapies.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The short-term nature of the clinical follow-up, especially in the efficacy study, restricts our ability to assess the long-term effects of the helenalin-based formulation. On the other hand, the rapid and multi-targeted efficacy of the studied formulation aligns with previous outcomes of similar studies that blocked NF-κB/TNF-α pathways [ 65 , 74 , 75 ]. It is important to recognize that the rapid improvement observed in this study may not be representative of the standard response across all DED therapies.…”
Section: Discussionsupporting
confidence: 85%
“…The exact mechanisms behind NF-κB activation in DED are not fully understood. Still, oxidative stress and continuous tear film hyperosmotic stress are believed to contribute to its dysregulation, leading to persistent inflammation in the cornea and conjunctiva of DED patients [ 64 , 65 ]. NF-κB activation pathways release pro-inflammatory cytokines (such as IL-1b, IL-2, IL-6, IL-8, IL-12, and TNF-α) and chemokines (MCP-1, IL-18, and CXCL 10), which can not only trigger an inflammatory response but also lead to goblet cell loss.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pathological alterations were detected in the cornea and lacrimal glands of the diabetic rat models. The relationship between changes in cornea thickness and diabetic dry eye remains unclear, but studies have demonstrated that reduced corneal epithelial thickness is a diabetic complication (65,66). However, in the present study, the change in corneal thickness in diabetic rats was not reversed, although the intracellular vacuoles and acinar atrophy were ameliorated by APX-115A treatment in the diabetic rats.…”
Section: Discussioncontrasting
confidence: 75%
“…However, the DM + ART (50 mg/kg) and DM + INS intervention groups displayed normal lobular patterns and no acinar atrophy and fibrosis. The relationship between changes in cornea thickness and diabetic dry eye remains unclear, but studies have demonstrated that reduced corneal epithelial thickness is a diabetic complication [29][30][31] We have observed corneal epithelial staining was improved significantly with ART treatment. ART has also been shown to alleviate inflammatory cell infiltration in the lacrimal gland, increased cell nuclei, and fewer vacuoles were seen in the cortical region of the lens.…”
Section: Discussionmentioning
confidence: 69%